Alcohol Septal Ablation or Septal Myectomy? An Updated Systematic Review and Meta-Analysis of Septal Reduction Therapy for Hypertrophic Obstructive Cardiomyopathy - Zheng, Xifeng; Yang, Bin; Hui, Haosheng; Lu, Bing; Feng, Yinhui (Frontiers in Cardiovascular Medicine, 2022)
Objective To evaluate the safety and effectiveness of alcohol septal ablation (ASA) and septal myectomy (SM) for the treatment of hypertrophic obstructive cardiomyopathy. Methods We searched the PubMed, MEDLINE, EMBASE, and CBM databases for observational research articles related to ASA and SM published from the establishment of the databases to November 2021. All ultimate selected articles were highly related to our target. The Newcastle-Ottawa Scale was used to evaluate the literature quality. A fixed or random effect model was performed in the meta-analysis depending on the heterogeneity of the included studies. The Mantel-Haenszelt test with relative risk ratio (RR) and 95% confidence interval (CI) was used to measure the effect indicator of binary data, while the inverse variance method with weighted mean difference (WMD) and 95% CI was used to measure the effect indicator of continuous data. Results A totally of 3,647 cases (1,555 cases treated with ASA and 2,092 cases treated with SM) were included. The results of the systematic review indicated no statistically significant difference in postoperative all-cause mortality (RR = 0.82; 95% CI: 0.65–1.04; P = 0.10) between patients treated with ASA and SM, but both the reduction in the postoperative left ventricular outflow tract pressure gradient (WMD = 9.35 mmHg, 95% CI: 5.38–13.31, P < 0.00001) and the post-operative improvement on cardiac function, assessed by the grade of New York Heart Association (NYHA), compared to pre-operative measurements (WMD = 0.13; 95% CI: 0.00–0.26; P < 0.04) in the ASA group were slightly inferior to those in the SM group. In addition, both the risk of pacemaker implantation (RR = 2.83, 95% CI: 2.06–3.88; P < 0.00001) and the risk of reoperation (RR = 11.23, 95% CI: 6.21–20.31; P < 0.00001) are recorded at a higher level after ASA procedure. Conclusion Both ASA and SM have a high degree of safety, but the reduction in the postoperative left ventricular outflow tract pressure gradient and the improvement on cardiac function are slightly inferior to SM. In addition, both the risk of pacemaker implantation and the risk of reoperation are recorded at a higher level after ASA procedure. The operative plan should be chosen through multidisciplinary discussions in combination with the wishes of the patients and the actual clinical situation.